PENGARUH STRATEGI BRANDING TERHADAP PENINGKATAN NILAI TAMBAH UMKM - Wira Yudha Alam; Nahairiyah Najwa, Wisnu Adi Pratama; Nur Arifatus Syarifah, Ellen Ananda Elviana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia’s economy, contributing significantly to equitable development, job creation, and overall economic growth. However, MSMEs continue to face challenges such as limited resources, low innovation, and weak marketing strategies, which lead to stagnant sales and low product value added. One effective solution is the implementation of branding strategies that enhance competitiveness and strengthen consumer perceptions of product quality. This study aims to analyze the impact of branding strategies on increasing the added value of MSME products using a qualitative approach based on literature review. Data were systematically collected from scientific journals, books, and relevant reports discussing branding strategies, innovation, and the utilization of digital technology in MSMEs. The analysis employed a descriptive-thematic and content analysis approach to identify patterns, themes, and relationships among concepts. The findings reveal that branding strategies—particularly digital branding, packaging innovation, brand identity strengthening, continuous training and mentoring, and green branding—play a significant role in enhancing brand awareness, consumer loyalty, and product value. Branding not only contributes to increased sales but also creates emotional value, product differentiation, and opportunities to access wider markets, including modern retail and international markets. Thus, branding can be regarded as a strategic instrument for MSMEs to achieve business sustainability and long-term competitiveness in the digital era.